1982
DOI: 10.1002/jcp.1041130127
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of hemoglobin accumulation and commitment during murine erythroleukemia cell differentiation by treatment with imidazole

Abstract: The effect of imidazole on DMSO-induced murine erythroleukemia (MEL) cell differentiation has been examined. While imidazole does inhibit heme, globin mRNA, and hemoglobin accumulation in DMSO-induced MEL cells, it does not affect the commitment of MEL cells to the specific limitation of proliferative capacity associated with the in vitro differentiation program. Furthermore, imidazole treatment does not affect DMSO-induced changes in cell volume, in the relative proportion of nuclear protein IP25, and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

1984
1984
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
0
21
0
4
Order By: Relevance
“…13,25 Several studies have indicated that the coordination of these programs is not obligatory. In this study we found that, although Bcl-X L antisense transcripts affect MEL cells in their ability to synthesize hemoglobin with DMSO, they have no effect on the proliferative aspect of the erythroid differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,25 Several studies have indicated that the coordination of these programs is not obligatory. In this study we found that, although Bcl-X L antisense transcripts affect MEL cells in their ability to synthesize hemoglobin with DMSO, they have no effect on the proliferative aspect of the erythroid differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the coordination of both programs is not obligatory. 25 That is why we examined the effect of Bcl-2 and Bcl-X L on loss of proliferative potential cell in DMSO-treated MEL cells. To study the loss of proliferative potential after DMSO induction, cells were cultured in suspension and diluted every 2 days.…”
Section: Transfection With Antisense Bcl-x L Induces Premature Apoptomentioning
confidence: 99%
“…HMBA and Me2SO are polar planar compounds that induce MELC to both terminal cell division and hemoglobin accumulation (11,19). Hemin induces MELC to accumulate globin mRNAs but does not cause commitment to terminal cell division (14,20,21). After 2 hr (62 hr after initiation of culture) with HMBA, Me2SO, hemin, or no addition, 56%, 27%, 11%, and 8% of MELC were committed.…”
Section: Effect Of Inducer Onmentioning
confidence: 99%
“…The benzidine reagent measures only heme biosynthesis, which under some conditions can be dissociated from terminal differentiation (15,16). We therefore asked whether pMbml-dhfr-transfected F-MEL clones also were inhibited in other differentiated functions.…”
mentioning
confidence: 99%